Kegiatan Magang melalui Pendampingan pada Nasabah Perempuan Pelaku Usaha Mikro pada PT Bank BTPN Syariah Tbk - Reski, Seyla (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
In this internship activity the author accompanied the customers of Shariah BTPN who are micro enterprise actors especially mothers from pre-welfare societies to empower their enterprises with materials tailored to the type of enterprises within a specified time frame for the capacity of the actors with the purpose of giving UMKpandakan knowledge and skills of business actors. Companion facilitators are tasked with empowering the Indonesian community through enterprise coaching material and active companionship. Certified Internship and Independent Study Program (MSIB) batch 7 with PT. Bank BTPN Shariah as a companion facilitator is a container where students can collaborate with customers who play a role in the advancement of customers’ enterprises, so in this case students can apply the knowledge gained on campus for self-actualization and directly contribute also can develop professional experience, specialized internship in terms of direct competencies for community empowerment. The program assists customers in developing efforts to improve their living standards that have great potential to create more significant socio-economic change.